Present consequences of the post-war migration in the Czech borderland for regional development - Vaishar, Antonín; Dvořák, Petr; Nosková, Helena; Zapletalová, Jana (Quaestiones Geographicae, 2017)
Czechia lost more than 3,000,000 inhabitants as a result of the WW II. Germans displaced from the borderland formed the largest part. The newcomers after 1945 were of a different character – without any relation to their new settlements. This population formed a special social milieu familiar with the socialist way of thinking and that of a suppressed middle class. The consequences of it are seen in demographic, economic, environmental and social areas. After 1989, the factories in the borderland were mostly closed down, armies left the territory, people were not prepared to start their own businesses. Large-scale landscape protection formed a new barrier. Tourism is not able to substitute for the decrease in employment. The hope in cross-border collaboration has been overestimated.